THE EFFECT OF CREATIVE THINGKING ABILITY AND BASIC MATHEMATICS ABILITY TOWARD STUDENTS PROBLEM SOLVING ABILITY - Made Subawo (JME (Journal of Mathematics Education), 2022)
ABSTRACTThis research is an ex post facto research with a quantitative approach. The population in this study were all class VIII of SMP Negeri 2 Ladongi with a total of 73 students. Using total sampling technique so that a total sample of 73 students is obtained. Data collection techniques using tests. Data analysis using multiple regression analysis.The conclusions in this study are as follows: (1) Decryptively, students' mathematics creative thinking abilities are in the quite creative category, students' basic mathematics abilities are in the medium category, students' mathematics problem solving abilities are in the low category; (2) there is a significant influence of students' mathematics creative thinking skills on mathematics problem solving abilities with thitung  ttabel  8,81 1,666 and sig α atau 0,001 0,05; (3) There is a significant positive effect on basic mathematics ability on mathematics problem solving ability with thitung  ttabel or 3,10  1,666 and sig α atau 0,004 0,05; (4) There is a significant positive influence on mathematics creative thinking skills and basic mathematics abilities on the mathematics problem solving abilities of class VIII students of SMP Negeri 2 Ladongi with FHitung = 65,71  or FTabel  = 3,13 or FHitung  FTabel  and significance = 0.000 α = 0.05. Keywords: Creative Thinking Abilities, Basic Mathematics Abilities, Problem Solving Abilities.